2006
DOI: 10.1111/j.1600-065x.2006.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of liver tolerance

Abstract: The liver exhibits a distinctive form of immune privilege, termed liver tolerance, in which orthotopic liver transplantation results in systemic donor-specific T-cell tolerance, while antigens introduced either into hepatocytes or via the portal vein also cause tolerance. Here we argue that the fundamental mechanism driving liver tolerance is likely to be the continuous exposure of diverse liver cell types to endotoxin, derived from the intestinal bacteria. This exposure promotes the expression of a set of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
175
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 163 publications
0
175
0
2
Order By: Relevance
“…Although KCs in HBV-carrier mice did not exhibit any obvious tolerance-associated phenotypic changes (Fig. S6), which may be explained by residing in a sustained typical liver-tolerant environment (1,25), these data strongly suggest that KCs contribute to systemic immune tolerance by inducing HBV-specific Tr1-like cell generation in an IL-10-dependent manner. (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although KCs in HBV-carrier mice did not exhibit any obvious tolerance-associated phenotypic changes (Fig. S6), which may be explained by residing in a sustained typical liver-tolerant environment (1,25), these data strongly suggest that KCs contribute to systemic immune tolerance by inducing HBV-specific Tr1-like cell generation in an IL-10-dependent manner. (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…peripheral tolerance | unresponsive T he liver is a unique organ that favors induction of immune tolerance rather than immune activation (1)(2)(3). It was reported 40 y ago that primary liver transplant induced a recipient pig to accept other allograft organs from the same donor (4), which suggested that the liver not only maintained the selftolerance, but also induced systemic tolerance in an antigenspecific manner.…”
mentioning
confidence: 99%
“…160,161 Alternatively, as NKT cells play a major role in liver-mediated tolerance, GC may exert it effects in the liver. 102,[162][163][164] Finally, as CD1d molecules are highly expressed in the bowel, and as both DCs and NKT cells play a role in mucosal immunity in the bowel, GC may exert its effect on the gutassociated lymphoid tissue. [165][166][167] GC AS A THERAPEUTIC AGENT IN HUMANS An altered number or function of NKT cells has also been described in several human autoimmune diseases.…”
Section: Sites For Action Of Gcmentioning
confidence: 99%
“…In addition, Kupffer cells constitutively express many proinflammatory cytokines including IL-10,TGF-β, IL-1, IL-6, IL-12, IL-18, tumor necrosis factor α, and indoleamine 2,3-dioxygenase, and may modulate differentiation and proliferation of other immune cells in the liver. 18,38,39 This suggests that Kupffer cells maybe important in regulating immunoreactions in the liver and contributing to liver-mediated systemic immune tolerance. 40 The liver hosts several other important cell types including hepatic stellate cells, liver sinusoidal endothelial cells, and radiation-resistant sessile Kupffer cells.…”
Section: Liver Nonparenchymal Cells and Tolerance Inductionmentioning
confidence: 99%
“…17 Furthermore, the liver is the site of persistent viral infections such as hepatitis B and hepatitis C, possibly because of an ongoing immune response that fails to clear the virus. 18,19 Therefore, the liver has the unique immunologic property of inducing tolerance to alloantigens.…”
Section: Establishment Of Liver Tolerancementioning
confidence: 99%